DIFFERENT CLINICAL PRESENTATIONS OF PARAGANGLIOMA FROM TWO DIFFERENT ORIGINS: A CASE SERIES - Ramli, Fathiyah; Ali, Masliza Hanuni Mohd; Azman, Siti Sanaa Wan; Omar, Syed (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Paragangliomas are rare neuroendocrine tumours that arise from extra-adrenal paraganglia. Presentation can vary based on the anatomic origin. Sympathetic paragangliomas typically manifest with classic adrenergic symptoms. Here we present two cases of functional paraganglioma from two different origins. CASE A 25-year-old Malay female was diagnosed with pregnancy-induced hypertension during her last pregnancy 3 years ago, necessitating admission for impending eclampsia at 37 weeks. She complained of palpitations and chest pain. Post-partum, she remained hypertensive. A workup for secondary hypertension revealed marked elevation of 24-hour urine normetanephrines, 36 times the upper limit of normal (95.42 umol/day) and 2.5 times the elevation of 3-Methoxytyramine (4.46 umol/day). Adrenal CT showed a well-defined, enhancing lesion at the aortocaval region, measuring 5.1×5.8×7.0 cm. CT scans of the neck and thorax were unremarkable. A Gallium-68 PET scan demonstrated SSTR-avid uptake in the aortocaval mass, with no evidence of SSTR-avid disease elsewhere. Currently, she requires three antihypertensive agents to control her blood pressure while awaiting surgical intervention. A 67-year-old Malay female with underlying hypertension, diabetes, and ischaemic stroke had multiple admissions for urosepsis. Ultrasound revealed a bladder mass suspicious for malignancy, a left ureteric stone, and hydronephrosis. CT and MRI showed a 4.0×3.6×3.7 cm heterogeneously enhancing mass arising from the right lateral bladder wall. She underwent transurethral resection of bladder tumour (TURBT); intraoperatively, her blood pressure was labile with systolic BP of 65–320 mm Hg. Histopathology confirmed paraganglioma. Post-operative 24-hour urine normetanephrines were four times the upper limit of normal. Due to her poor performance status, she was managed conservatively. Her blood pressure is currently controlled on double antihypertensives. CONCLUSION Paragangliomas can present variably depending on their anatomical origin and catecholamine-secreting status. A high index of suspicion, appropriate biochemical testing, and functional imaging are key to diagnosis. Individualized management is essential, especially in patients with comorbidities or poor performance status.